ANALISIS SISTEM PENGELOLAAN KEUANGAN DANA DESA NAGORI MARIHAT BARIS KECAMATAN SIANTAR KABUPATEN SIMALUNGUN - Simare-Mare, Putri Ade Nopita Sari; Sembiring, Sabeth (LPPM Universitas Katolik Santo Thomas Medan, 2024)
This research aims to determine the financial management system for Nagori Marihat Baris village funds, Siantar District, Simalunggun Regency. Meanwhile, data collection was carried out using interviews and documentation. The population in this research is the budget report and realization of Nagori Marihat Baris village funds from 1975-2023. The sample in this research is the budget report and realization of village funds in 2021-2022 with all village officials and the Nagori Marihat Baris community. The method in this research uses a qualitative descriptive method. The results of this research show that the financial management system for Nagori Marihat Baris village funds uses the Siskuedes application system which makes it easier to operate in conveying activities and programs for the activities carried out, however there are several stages of financial management of village funds in Permendagri No. 20 of 2018 that are still not appropriate based on financial management system, among others: 1). Related planning is the design mechanism for village fund management planning, minimizing wasted costs, integrating policies or opinions, principles and technical preparation.2). The related implementation is revenue and expenditure, making a budget plan for activity costs and carrying out activities, being responsible for the implementation of activities. 3). Related administration is managing village finances, recording every incoming and outgoing budget and closing the cost budget book. 4). Related reporting is submitting implementation realization reports to superiors, knowing the progress of implementing activities and transparency. 5). The related accountability is submitting a realization accountability report and an accountability report submitted no later than 3 months after the end of the relevant budget year as determined by village regulations.